Comprehensive genomic and functional characterization of a phytoplasma associated with root retardation, early bolting, witches’-broom, and phyllody in daikon (Raphanus sativus L.) - Chiu, Yi-Ching; Lin, Yu-Chen; Pao, Shang-Hung; Chen, Yuh-Kun; Liao, Pei-Qing; Mejia, Helen Mae; Sheue, Chiou-Rong; Kuo, Chih-Horng; Yang, Jun-Yi (Frontiers in Microbiology, 2025)
Daikon (Raphanus sativus L. var. longipinnatus) is an economically important root crop and medicinal plant. In 2021, a previously unreported disease outbreak characterized by early bolting, witches’-broom, phyllody, virescence, and severe root growth retardation was observed in daikon fields in Yunlin, Taiwan. Transmission electron microscopy revealed pleomorphic phytoplasma-like bodies within the sieve elements of symptomatic plants. Molecular diagnostics and phylogenetic analyses identified the causal agent as a 16SrII-A subgroup strain of ‘Candidatus Phytoplasma aurantifolia’, designated NCHU2022. Hybrid genome assembly using Illumina and Oxford Nanopore sequencing yielded a complete genome consisting of a 632 kb circular chromosome and a 4.2 kb plasmid. Effector prediction and functional assays identified two secreted proteins, SRP06 and SRP15, homologous to SAP54/PHYL1 and SAP11, respectively, which induced phyllody and witches’-broom symptoms through destabilization of floral MADS-domain and class II TCP transcription factors. Transcriptomic profiling of infected roots revealed activation of auxin biosynthesis and signaling pathways, accompanied by suppression of cytokinin signaling and induction of lignin biosynthesis, suggesting that hormonal reprogramming contributes to abnormal root development. While previous studies have primarily focused on aerial symptomatology—such as witches’-broom, phyllody, and sterility—our findings highlight an underexplored dimension of phytoplasma pathology: the profound impairment of root development driven by auxin dysregulation and associated transcriptional remodeling.